THE EFFECT OF SUPPLY CHAIN COLLABORATION ON SUPPLY CHAIN PERFORMANCE THROUGH PRODUCTION TECHNOLOGY, NEW PRODUCT DEVELOPMENT, AND PRODUCT KNOWLEDGE - Enny Novijanti; Hotlan Siagian (Petra Christian University, 2024)
Manufacturing companies are making a quick effort in anticipation of erratic business changes. Internal changes were made to adapt to the company's external conditions. Partnerships are needed to connect internal and external parties through supply chain collaboration, thereby improving supply chain performance and increasing competitiveness. Data collection from 99 manufacturing companies. The hypothesis was tested using partial least squares software. The data processing results indicate that supply chain collaboration positively influences product technology, product knowledge, new product development, and supply chain performance. The company's product technology has a positive impact on improving product knowledge, new product development and supply chain performance. The results of the hypothesis test also show that supply chain performance is influenced by product knowledge and new product development. The contribution of the theory of research results to enrich supply chain theory in producing product technology, product knowledge, and company competitiveness. A practical contribution is to provide guidance for company managers to carry out supply chain collaboration to improve performance and competitiveness.